Integrated Cytology of Cerebrospinal Fluid - Torzewski, Michael; Lackner, Karl J.; Bohl, Jürgen; Sommer, Clemens (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Cytologic examination of the cerebrospinal fluid is a technically simple, yet productive, diagnostic procedure. Integrated Cytology of Cerebrospinal Fluid is a practical guide to this method used in the diagnosis of different pathologies. High-quality slides depict the common cerebrospinal fluid cell types, cell anomalies in inflammatory conditions and neoplastic and non-neoplastic disorders, and cases with contaminants. The integrated approach includes the use of immunocytochemical, histological, and immunohistological illustrations and quantitative date in addition to descriptions and photographs of cytologic preparations.